تنمية مهارة القراءة العربية باستخدام شبكات التواصل الاجتماعية - شيرازي، وئام محمد (Kulliyah of Education, International Islamic University Malaysia, 2016)
This study aimed to identify the students' attitudes toward learning Arabic reading using WhatsApp group, and also examine the flexibility and effectiveness of WhatsApp application as a way to learn Arabic reading; it is also aimed to investigate the effect of using WhatsApp in learning Arabic reading. Moreover, this study wants to see how much students having fun learning and satisfaction during communicate via WhatsApp to learn Arabic reading. This study is a quantitative study using the descriptive and analytical approach as the appropriate approach for studies that aim to describe the phenomenon as it is in reality. It was a purposive choice sampling of 80 students were selected for their expertise in the use of WhatsApp in learning. They are bachelor students of the Faculty of Education Department of Teaching of Arabic to Non-Arabic Speakers in the International Islamic University Malaysia's second academic year 2015/2016 M. It was distributed a questionnaire adapted from three previous studies and was modified by the researcher where 30 items divided on three main constructs, which are flexibility and effectiveness, the impact of the use of WhatsApp in learning Arabic reading, and enjoyment and satisfaction. The questionnaire was distributed electronically via the Internet (Google Form) and the 80 students were responded to them. The results showed that students have positive attitudes towards learning Arabic reading using WhatsApp group, as indicated by a high level of agreement to respond to the questionnaire items. It also became apparent high flexibility and effectiveness in using WhatsApp as a way to learn Arabic reading with high level of agreement. It is also incated that there is a significant impact on the use of WhatsApp to learn Arabic reading. The results also showed that students feel the joy of reading to learn Arabic and satisfaction using WhatsApp.